Investigation of intermolecular interactions of l-Valine and l-Phenylalanine with muscle relaxant drug mephenesin molecule prevalent in aqueous solution by various physico-chemical methods at T=298.15K–313.15K - Baishali Saha; Sanjoy Barman; Sukdev Majumder; Biswajit Ghosh; Kangkan Mallick; Subhankar Choudhury; Mahendra Nath Roy (Heliyon, 2024)
A complete chemical analysis of significant intermolecular interactions of l-Valine (L-Val) and l-Phenylalanine (L-Phe) with Mephenesin (MEPN) molecules in aqueous solution has been studied by different physicochemical methodologies at various temperatures (T = 298.15 K–313.15 K at an interval of 5 K) and concentrations (0.001 mol kg−1, 0.003 mol kg−1, 0.005 mol kg−1) of aqueous MEPN solution. The limiting apparent molar volume (φV0) and experimental slope (SV*) values are found from the equation of Masson, viscosity A and B-coefficient determined using the equation of Jones-Doles, molar refraction (RM) and limiting molar refraction (RM0) derived by the Lorentz-Lorenz equation, express that in our experimental solution of amino acids (AAs) in aqueous MEPN, the solute-solvent interaction predominates over the solute-solute and solvent-solvent interactions for these ternary solutions. These are also justified by the measurement of various thermodynamic parameters, free energy of activation of viscous flow per mole of solvent(Δμ1°#) and solute (Δμ2°#), activation of viscous flow of enthalpies (ΔH°#) and entropies (ΔS°#). The characteristics of structure-breaking of solutes in the aqueous drug solution have been identified by Hepler's method and dB/dT value. The spectroscopic methods like UV–visible and proton-NMR studies help to explicate the strong AA-MEPN interactions in the solution phase and obtain a good correlation with theoretical studies. Theoretical investigations are checked to authenticate the experimental observations and according to both studies, L-Phe-MEPN interaction is greater than L-Val-MEPN interaction. The experimental and correlated research data are useful for the development of model combinations of AAs with drug molecules in pharmaceutical and medicinal chemistry.